(untitled) (Research, Society and Development, 2023)
The present article aims to evaluate by means of an integrative review the possible therapeutic interventions used for the systemic treatment of Stevens-Johnson Syndrome (SJS), such as toxic epidermal necrolise, or pathologies that are rare and serious. Within this aspect, it is known that systemic treatment is necessary, or which includes the use of medications such as corticosteroids, immunoglobulins and cyclosporine, possibly presenting an article or objective of addressing the characteristics of SJS and TEN, as the systemic treatment options available, The benefits and challenges of each treatment and its implications for the health of two patients. The study presents data and evidence regarding the two treatments currently available, validating the time of intervention and its respective effectiveness. Thus, articles are collected in the databases PUBMED, LILACS and SCIELO, as the forums published in the period from January 2012 to August 2023, in portuguese, english and spanish languages. Subsequently, a careful analysis of the pre-selected material was carried out, with the aim of gathering the most complete and relevant information on the subject matter of the article. This review concludes that despite the infinite number of possibilities, the use of biological TNF-alpha inhibitors and systemic corticosteroids is the most effective.